Controlled synthesis of carbon-coated cobalt sulfide nanostructures in oil phase with enhanced Li storage performances - Shi, Wenhui (2013)
A novel solvothermal process was developed for the synthesis of carbon-coated Co9S8 nanodandelions using 1-dodecanethiol as the sulfur source and the soft template. Replacing 1-dodecanethiol with sulfur powder as the sulfur source leads to the formation of 20 nm Co9S8 nanoparticles without carbon coating. When tested as LIB anode, the C@Co9S8 dandelion delivers a specific capacity of 520 mA h g–1 at a current density of 1 A g–1 (1.8 C) during the 50th cycle, which is much higher than that of Co9S8 nanoparticles (e.g. 338 mA h g–1). Furthermore, the C@Co9S8 dandelion also exhibits excellent high C-rate performance, e.g., depicts a 10th-cycle capacity of 373 mA h g–1 at a current density of 6 A g–1 (10.9 C), which is better than that of many reported anode materials. Such synthesis approach is attractive for the preparation of sulfide anode materials with high Li storage properties.